The Fund's Income Position for FY 2012 : Actual Outcome. (Policy Papers; Policy Paper, 2012)
This paper presents the Fund's net income for FY 2012. The actual outcome reported in this paper follows the closing of the Fund's accounts for the financial year and completion of the FY 2012 external audit conducted by Deloitte and Touche, the Fund's external auditor.